Malik Bennabi's Concept of Culture, as Presented in his Book "Problems of Civilization and Conditions of Renaissance" and its Quranic Foundations: An Analytical Study - Youcha Alassane Toure (Al Karima : Jurnal Studi Ilmu Al Quran dan Tafsir, 2026)
This study aims to analyze the concept of culture in the thought of Malik Bennabi through his book Mushkilat al-Hadarah wa Shurut al-Nahdah, by examining the nature of this concept and its function in the construction of both the individual and society. The study is grounded in the significance of culture as a central concept in explaining the problems of civilizational decline in Muslim societies. This research employs a descriptive-analytical method by examining Bennabi’s texts and analyzing their content within their intellectual and civilizational context. The findings reveal that culture, according to Malik Bennabi, constitutes a fundamental core in the formation of civilization and is not merely an intellectual ornament, but rather an integrated system of values and norms that shape human behavior, regulate the relationship between the individual and society, and determine one’s worldview. The study further concludes that genuine renaissance cannot be achieved without reforming the cultural structure of society, as it serves as the foundation for developing an active individual capable of contributing to civilization.